Tradisi Babore dalam Pengobatan Tradisional Basanggar pada Suku Dayak Ahe di Desa Sekabuk, Kecamatan Sadaniang, Kabupaten Mempawah - Miki, Klarasia Oktaviani; Praptantya, Donatianus BS; Batuallo, Ignasia Debby (Universitas Tanjungpura, 2024)
This study aimed to delve into or depict deeply the phenomenon of the Babore tradition, which is one of the cultures and traditions among the Dayak Ahe community in Sekabuk Village. This study also aimed to describe the process of conducting Basanggar and how it was conducted among the Dayak Ahe community in Sekabuk Village of Sadaniang District in Mempawah Regency. The research site of this study was Sandaniang District, specifically Sekabuk Village. This study used Robert R. Redfield’s theory with the concept big and small traditions. This study employed a qualitative research method with an ethnography approach, which was categorized as a qualitative research design. The results of this study revealed the process of conducting the Babore tradition in traditional treatment.